Gourd, Ornamental—Lagenaria spp., Cucurbita spp., and Luffa spp. - James M. Stephens (EDIS, 2003)
This document provides an overview of ornamental gourds from the genera Lagenaria, Cucurbita, and Luffa, highlighting their diverse shapes, colors, and textures. It describes their growth habits, cultivation methods suitable for Florida, and post-harvest handling. The gourds, often grown for decorative purposes, can also be crafted into practical items such as birdhouses, bowls, and sponges. The article emphasizes the aesthetic and utilitarian value of these hard-shelled fruits, detailing popular varieties and offering guidance on drying, curing, and creative uses. Original publication 1994.